"Savoring" buffers the association between negative emotions and suicidal behaviors in the GSM community. Issue 1 (2nd January 2019) - Klibert, Jeffrey J.; Luna, Amy; Miceli, Matthew
Abstract: This study examined the effects of "savoring the moment" (the ability to generate, maintain, and extend positive emotions) on the relationship between negative emotions and suicidal behavior in a sample of gender and sexual minorities (GSM). Savoring the moment moderated the associated effects of negative emotions on suicidal behavior; the relationship between negative emotions and suicidal behaviors ceased at higher levels of savoring the moment. Our finding offers preliminary evidence for savoring as a buffer to suicide among subpopulations of GSM individuals. Our findings also provide some insights into the use of positive psychological interventions in GSM suicide prevention efforts.